Bathymetry of the South African Continental Shelf - de Wet, Willem Myburgh (Department of Geological Sciences, 2018)
South Africa has an extensive coastline offshore of which lies the prominent South African continental shelf, a relatively flat extension of the onshore coastal plain. The continental shelf is host to major mineral and petroleum deposits, home to South Africa’s major sea fisheries and full of navigation hazards. Therefore, knowledge of the seafloor features, or bathymetry, of the continental shelf is essential to understanding both its long-term geological evolution and present-day use for resources and navigation. Unfortunately there has been little advancement in our knowledge of the South African continental shelf since the marine studies of the 1970’s and 1980’s which culminated in the “Bathymetry around Southern Africa” map of Dingle et al. (1987).